Attitudes of Preschool Teachers towards Artificial Intelligence - Kardeş, Servet; Uygun, Nur; Terim Türkmen, Tuba (Southeast Asia Early Childhood Journal, 2025)
Due to the developments in the field of artificial intelligence, artificial intelligence-supported education has begun to show more effectiveness in the field of early childhood. There are studies indicating that the use of artificial intelligence in early childhood education improves children's learning processes. Therefore, this study aimed to reveal the attitudes of preschool teachers towards the use of artificial intelligence in education. The explanatory design from mixed method designs was used in the study. The quantitative data of the study was obtained from interviews with 120 preschool teachers and qualitative the data was obtained from interviews with 10 preschool teachers. As a result of the study, it was revealed that the attitudes of preschool teachers towards artificial intelligence did not differ according to age and work experience, but differed according to gender. It was revealed that preschool teachers generally supported the use of artificial intelligence in preschool education. Another result was that preschool teachers with high skills in using technological devices had more negative attitudes towards artificial intelligence than teachers with low skills in using technological devices. Suggestions were presented in line with the results of the study. Finally, preschool teachers stated that artificial intelligence cannot be used in preschool education due to lack of equipment, costs, insufficient expertise in artificial intelligence, and artificial intelligence not being suitable for children's development. In line with the research results, trainings and programs can be developed to support preschool teachers' self-efficacy in digital literacy and artificial intelligence use. It can be recommended that the necessary infrastructure and systems for the use of artificial intelligence be provided to preschool learning environments and that this be offered to all institutions on the basis of equal opportunities.